Age chronology based on aminae count and year of collection (2012) of Stalagmite GL-S4 from the Golgotha Cave in southwest Western Australia - Pauline C Treble; Andy Baker; Nerilie J Abram; John C Hellstrom; Jagoda Crawford; Michael K Gagan; Andrea Borsato; Alan D Griffiths; Petra Bajo; Monika Markowska; Stacey Priestley; Stuart I Hankin; et al. (PANGAEA, 2022)
Stalagmite GL-S4 chronology (CE) based on laminae count and year of collection (2012). This laminae count is the chronology used in Treble et al (2022).
In: Treble, PC et al. (2022): Golgotha Cave stalagmite records 1 ka [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.941440